Analysis and Evaluation of Piezometric Measurements in Al- Basel Dam in Tartous - غنم, عروة; منذر حمّاد , (Latakia University Journal -Engineering Sciences Series, 2024)
Piezometric measurements contribute to giving a clear idea of the levels of seepage water and their changes over time, and provide a suitable database for analysis and to show any emergency structural or hydraulic problem resulting from the seepage, interpret it, and determine its causes. This study aims to analysis the piezometric measurements in in Al- Basel dam in Tartous, by studying the changes in water levels in the piezometric wells in relation to the storage levels in the reservoir, and link them to a specific relationship, to form a guideline that enables us to detect any emergency problem or any wrong measurement and take or suggest the necessary measures to confirm and process them. The study revealed that significant changes in water levels occurred in some of the crest wells, requires investigation and identification of the causes. Therefore, three scenarios were proposed to find out the cause of the problem and build mathematical models using the SEEP/W program. Analysis the results showed the presence of a clogging in the first filter layer as a result of soft, erosion materials being placed in it, coming from the core or materials resulting from the oxidation of water with soil compounds, accurate analysis requires collecting samples water from wells and conducting the necessary analyses.